2012
DOI: 10.2174/1874325001206010406
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of TGF-β1 And BMP–7 on Chondrogenesis and Extracellular Matrix Synthesis: An In Vitro Study

Abstract: Introduction:The purpose of the present study seeks to determine the signal timing of BMP–7 and TGF-β1 from a novel chitosan based hydrogel system that may affect chondrocyte proliferation resulting in the presence of a synergism seen conspicuously in consecutive controlled delivery.Methods:Four groups of cultured chondrocytes were seeded on a novel designed chitosan based hydrogel. The hydrogel was left empty (control) in one group and loaded with BMP–7, TGF-β1 and their combination in the other groups, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 29 publications
3
40
0
Order By: Relevance
“…Some studies suggested that BMP- 2 had the ability to facilitate cartilage formation by chondrocytes and MSCs for treatment of cartilage and osteochondral defects [45, 249, 250]. BMP- 7 was used in cell-laden hydrogel constructs for promoting chondrogenesis and cartilage ECM formation [251]. Extensive research has shown that BMPs are effective growth factors to regulate both cartilage and bone formation.…”
Section: Effects Of Growth Factors and Delivery Methods On Chondromentioning
confidence: 99%
“…Some studies suggested that BMP- 2 had the ability to facilitate cartilage formation by chondrocytes and MSCs for treatment of cartilage and osteochondral defects [45, 249, 250]. BMP- 7 was used in cell-laden hydrogel constructs for promoting chondrogenesis and cartilage ECM formation [251]. Extensive research has shown that BMPs are effective growth factors to regulate both cartilage and bone formation.…”
Section: Effects Of Growth Factors and Delivery Methods On Chondromentioning
confidence: 99%
“…MTT analyses were evaluated in accordance with commercial kit bulletins on the 1st, 7th, 14th, and 21st days [1520, 24, 26]. …”
Section: Methodsmentioning
confidence: 99%
“…The rhOP‐1 release from the scaffolds over a 28‐day period was evaluated using an enzyme‐linked immunosorbent assay (ELISA) kit # . The OP‐1 ELISA was performed according to an established protocol in 96‐well plates with two control columns 24 . Absorbance was measured at 400 nm, and the result was compared with the control curve to give the OP‐1 concentration at each time period.…”
Section: Methodsmentioning
confidence: 99%